Importance of Sociology and Sociological Ethics, and Its Value on Bioethics Perspective - Chatterjee, Subhasish; Roy, Banibrata; Wadhwa, Medha (International Journal of Psychosocial Rehabilitation, 2020)
This pilot study has been undertaken with a primary objective to find the intersection of ‘bioethics and sociology.’ In this study, an effort is made to understand five different perspectives based on a sample of respondents and bringing several stakeholders, like sociologists, people from the medical fraternity, clinical practitioners, behavioral scientists, and bioethicists, onto the same platform. The authors have presented precise statistical reasoning after assembling useful data. This will empower the researchers to take appropriate decisions for further study. For this study, several literatures have been reviewed in determining an appropriate hypothesis, and accordingly, structured questionnaires were prepared for the collection of data. The collected data were analyzed using non-parametric inferential statistics (Kolmogorov-Smirnov Goodness of Fit Test and Sign Test) for testing five hypotheses. The study is concluded based on inference research so that the researcher can make more effective and efficient decisions to enhance the future research study of the significance of sociology on bioethics in a broader range.